RESEARCH-BASED INDEPENDENT CURRICULUM MANAGEMENT AT SMA GENIUS: MANAJEMEN KURIKULUM MERDEKA BERBASIS RISET DI SMA GENIUS - Febriani Dwi Sari; Masduki; Desi Rahmawati (SOSIOEDUKASI, 2025)
The implementation of the research-based Independent Curriculum in Indonesia faces complex challenges, especially in accommodating students from disadvantaged areas with high heterogeneity of backgrounds. This study aims to analyze the management of the research-based Independent Curriculum at SMA GenIUS and identify the factors that affect the effectiveness of its implementation in students from Eastern Indonesia. The research method uses a qualitative approach with a case study at GenIUS High School, involving the principal, vice principal, 15 teachers, and observation of the implementation of the Re-Search program. Data collection techniques through in-depth interviews, participatory observations, and analysis of curriculum documents. Data were analyzed using Miles & Huberman's thematic analysis technique. The results of the study show that the management of the research-based Independent Curriculum at SMA GenIUS includes four main stages: planning by mapping the level of inquiry through diagnostic tests, organizing differentiated learning in the classroom, the implementation of the Re-Search program with four levels of inquiry (confirmation, structured, guided, open), and holistic evaluation using rubrics and STS assessments. Supporting factors include data-driven documentation systems, collaboration with universities, and the commitment of school management. Meanwhile, the inhibiting factors are the heterogeneity of students' abilities in one class and the need for structured learning modules. The implementation of the Re-Search program improves students' critical thinking skills and research literacy, with the student involvement rate reaching 85% in the selection of research topics according to personal interests.